2018
DOI: 10.4018/978-1-5225-5164-5.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Survey Research Using MTurk

Abstract: This chapter presents an introduction to crowdsourcing for survey participant recruitment. It also discusses best practices and ethical considerations for conducting survey research using Amazon Mechanical Turk (MTurk). Readers will learn the benefits, limitations, and trade-offs of using MTurk as compared to other recruitment services, including SurveyMonkey and Qualtrics. A synthesis of survey design guidelines along with a sample survey are presented to help researchers collect the best quality data. Techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…SurveyMonkey email platform was used to administer the questionnaire via e-mail invitations with a cover letter. This was done following the provisions of Chambers and Nimon (2019).…”
Section: Methodsmentioning
confidence: 99%
“…SurveyMonkey email platform was used to administer the questionnaire via e-mail invitations with a cover letter. This was done following the provisions of Chambers and Nimon (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the quality of the collected data is subject to potential bias. Participants received monetary compensation, raising concerns about the presence of professional survey takers who might inaccurately present themselves while participating in the study [88] and/or not provide thoughtful responses. Future studies should employ multiple methods of data collection to overcome this limitation.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…According to the World Bank Report in 2015, MTurk had a population of people worldwide (Pew Research Center 2016). Despite concerns about the external validity of MTurk, studies showed the reliability of the data gathered using this platform (Chambers and Nimon 2017). The external validity was also demonstrated by comparing it with data gathered in a laboratory or using a university sample (Behrend et al 2011).…”
Section: Data Collectionmentioning
confidence: 99%